Gigantic lipoma of subperitoneum - Matteucci, Pablo; Armand Ugon, Alfredo; Sarroca, Carlos; López Susviela, Julio (Cirugía del Uruguay, 1977)
A patient developed a gigantic· lipoma of sub-peritoneum which had a 32 cm diameter and weighed 6 149 Frc. 3.- Corte histológico. Debe destacarse la congestión e infiltración hemorrágica. kilos. Histological study showed none of the malignant patches, which are usual in very large lipomas.